Enhancing meat product quality: Exploring the effects of additives on Myofibrillar protein functionality - Nurul Shaeera Sulaiman; Mohd Dona Sintang; Nurul Huda; Hana Mohd Zaini; Md. Jahurul Haque Akanda e; Wolyna Pindi (Springer Science+Business Media, LLC, part of Springer Nature, 2025)
Additives are utilized in the production of high-quality meat products to minimize costs and fulfill consumer demands for healthier food choices. However, a comprehensive summary of the structural and functional changes in myofibrillar protein (MP) during gel formation in response to various additives is lacking in the literature. Nonetheless, this in-depth review revealed that additives affect the denaturation process of MP, which indirectly controls the crosslinking and impacts the functionalities of MP. Specifically, additives improve the inter- and intra-interaction of MPs during processing. Therefore, a mechanistic understanding of the impact of each additive on MPs from different sources is needed. Different sources of MP have different compositions, thus resulting in different functionalities. A discussion of these issues is also provided in this review. This discussion also focuses on the current approaches to understanding the functional changes in MPs caused by different additives and presents some examples of previous works and the progress made in the literature.